Review paper Hormonal contraception and risk of sexually transmitted disease acquisition - Łącka, Katarzyna; Żaba, Ryszard; Zachwieja, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Worldwide, an increasing number of women are deciding to use hormonal contraception. This review presents the current knowledge of the effect of this contraceptive method on the risk of sexually transmitted disease acquisition. Several studies suggest that hormonal contraception users are at increased risk of sexually transmitted diseases. However, many other studies did not demonstrate it. It is proved that using hormonal contraception may have a protective effect on bacterial and trichomoniasis infection. Moreover, the risk of infection is positively associated with the composition of hormonal contraception and women's lifestyles.